LEGAL IMPLICATIONS OF THE CONSTITUTIONAL COURT DECISION ON THE APPLICATION OF RESTORATIVE JUSTICE CONCEPT IN INDONESIA - Hayatuddin, Khalisah; Suharyono, Suharyono; Sobandi, Sobandi; Is, Muhamad Sadi (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2022)
The decision of the Constitutional Court Number 68/PUU-XV/2017 cancels Articles 96, Articles 100, and Article 101 of Law Number 11 of 2012 on the Juvenile Criminal Justice System. With this decision, the concept of restorative justice in Indonesia evolves even a stronger legal basis. In this paper, the research method that the researcher uses is a normative juridical legal method that is prescriptive means practical or applicable. This research aims to solve the problems of the research. The results of this study explain that after this decision of the Constitutional Court has been set, it implicates the law,Â which is the development of the ideal concept of restorative justice in Indonesia, that is regulated clearly and firmly in the Criminal Code, the Prosecutor's Law, and the Police Act, which can provide legal certainty regarding restorative justice so that it can realize the concept of restorative justice which conducting deliberation process by listening to and reassuring the aggrieved parties based on the philosophical values of the Indonesian nation that can provide social justice for all Indonesian people.